2017
DOI: 10.1038/nature23467
|View full text |Cite
|
Sign up to set email alerts
|

Type III CRISPR–Cas systems produce cyclic oligoadenylate second messengers

Abstract: In many prokaryotes, type III clustered regularly interspaced short palindromic repeat (CRISPR)-CRISPR-associated (Cas) systems detect and degrade invasive genetic elements by an RNA-guided, RNA-targeting multisubunit interference complex. The CRISPR-associated protein Csm6 additionally contributes to interference by functioning as a standalone RNase that degrades invader RNA transcripts, but the mechanism linking invader sensing to Csm6 activity is not understood. Here we show that Csm6 proteins are activated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
511
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 419 publications
(532 citation statements)
references
References 43 publications
19
511
1
1
Order By: Relevance
“…Recent studies have revealed an immune mechanism in the Class 1 Type III–A system that parallels the target-activated collateral cleavage by Cas13 (Kazlauskiene et al, 2017; Niewoehner et al, 2017). In this system, the multi-subunit Csm effector complex binds RNA transcripts that match the guide crRNA.…”
Section: Type VI Crispr–cas Systemsmentioning
confidence: 99%
“…Recent studies have revealed an immune mechanism in the Class 1 Type III–A system that parallels the target-activated collateral cleavage by Cas13 (Kazlauskiene et al, 2017; Niewoehner et al, 2017). In this system, the multi-subunit Csm effector complex binds RNA transcripts that match the guide crRNA.…”
Section: Type VI Crispr–cas Systemsmentioning
confidence: 99%
“…Future interkingdom microbial consortia design can also exploit the CRISPR-Cas systems, a microbial strategy to overcome 'invasions' by phages/viruses. While recent studies utilize CRISPR in monoculture systems (Donohoue et al, 2017), the new discovery of the signalling pathway between Cas and Csm complexes uncovered a future research direction of CRISPR regulation by controlling the signal messengers that activate the RNase activity (Kazlauskiene et al, 2017;Niewoehner et al, 2017). Although the CRISPR evolution and adaptation at the consortia level are still limited (Davison et al, 2016;Burstein et al, 2017), the manipulation of communication signals may be feasible in microbial consortia and further adapted to other biotechnological applications.…”
Section: Interkingdom Consortia Have Enhanced Tolerance Towards Extermentioning
confidence: 99%
“…To increase the sensitivity of the SHERLOCK system, a two‐step signal amplification protocol was developed using two different CRISPR effectors. Collateral ssRNA degradation by the Type III RNAse effector Csm6 is activated by the production of key second messengers that can be generated by the activity of Cas13. Using two different fluorescent reporters in the same channel with specificity to Csm6 or Cas13a, the sensitivity of SHERLOCK 2 could be further improved reaching nearly single molecule detection …”
Section: Novel Crispr‐based Tools For Cancer Diagnosticsmentioning
confidence: 99%